Improving EFL Students’ Learning Achievements and Behaviors using a Learning Analytics-based e-book System (International Conference on Computers in Education, 2020)
An e-book system allows students to access learning materials regardless of location or time. However, reading e-books without additional guidance could be inefficient for students and thereby affecting their learning engagement and learning outcomes. In this study, a learning analytics-based (LA) e-learning approach was proposed to resolve the situation. Moreover, experimental design methods were used to explore the relationship between the learning engagement, behavior, and achievement of students who learned with the LA e-learning approach. The research results show that the learning performance of high- engagement participants using the LA e-learning approach is better than that of low- engagement participants. In addition, the findings indicated that the proposed method could support low and medium learners to improve their learning achievement. These findings could be a valuable reference for those who intend to develop an effective learning analytics-based learning approach through e-book systems.